SWOT analysis of recruitment process at Badjoe M26 in improvement of business strategy - Nuraini, Rima; Sumadhinata, Yelli Eka (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research aim to analyze the recruitment process system for employees at the Badjoe M26 Warehouse Store, for knowing how is the recruitment process at the Badjoe M26 Warehouse Store, and for knowing the suitability of recruitment applied at the Badjoe M26 Warehouse Store. Types and approaches used that is Approach Qualitatively analyzed through SWOT analysis. Data collection is done Interview to the shop owner direct, and data from the results Interview then identified about internal and external factors using EFAS (External Strategic Factors Analysis Summary) and IFAS (Internal Strategic Factors Analysis Summary) matrices. score and weight of each internal and external factor like strength (Strength) of 2.88, Weakness is 0.44, Opportunity is 2.1 and Threat is 1.3. The total score of IFAS is 3.32 while the EFAS is 3.4. Research results show that position The Badjoe M26 Warehouse Store is in quadrant I which supports the Growth Oriented Strategy. This result signify the company have a good internal condition and a strong opportunity that will maximize source power more human quality and be capable innovate for successful effort undertaken.